Nivel de conocimiento sobre manejo de pacientes hipertensos de alumnos de IV y V nivel de una Facultad de Odontología de Iquitos-2025 - Briones Lanchi, Angel Gonzalo (2025)
Objective: To establish the difference in the level of knowledge between fourth- and fifth-year students at a dental school in Iquitos in 2025. Method: A quantitative, non-experimental, cross-sectional, descriptive comparative study was conducted. The sample consisted of 88 students from both the fourth and fifth years: 44 from the fourth year and 44 from the fifth year. A 27 question questionnaire on the management of hypertensive patients, validated by Ramos Zegarra (M.), was used. The data were analyzed using descriptive and inferential statistics. Results: The study found that the largest percentage of the sample had a fair level of knowledge (78.4%), followed by poor (14.8%) and good (6.8%) levels. It was also found that the level of knowledge among students by level was higher (93.6%) for Level IV students than for Level V students (61.0%). A relationship exists between the level of knowledge and the level of education (p=0.001). Conclusions: The largest percentage of the sample had a moderate level of knowledge. Furthermore, it was established that Level IV students had a higher percentage of knowledge than Level V students.